2013
DOI: 10.1007/s12033-013-9657-5
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Mapping and Molecular Diversity at the Flower Sex Locus in Wild and Cultivated Grapevine Reveal a Prominent SSR Haplotype in Hermaphrodite Plants

Abstract: Cultivars used for wine and table grape have self-fertile hermaphrodite flowers whereas wild European vines and American and Asian species are dioecious, having either male or female flowers. Consistent with previous studies, the flower sex trait was mapped as a single major locus on chromosome 2 based on a pure Vitis vinifera population segregating for hermaphrodite and female progeny, and a hybrid population producing all three flower sex types. The sex locus was placed between the same SSR and SNP markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
4
41
0
1
Order By: Relevance
“…The most parsimonious hypothesis we could make on sex inheritance in grape, based on previous observations, preliminary data analysis, and literature survey [6,7,17,18,20], was that of a XY system, where, at the sex locus, the female is homozygous (XX) and the male is heterozygous (XY).…”
Section: Methodsmentioning
confidence: 99%
“…The most parsimonious hypothesis we could make on sex inheritance in grape, based on previous observations, preliminary data analysis, and literature survey [6,7,17,18,20], was that of a XY system, where, at the sex locus, the female is homozygous (XX) and the male is heterozygous (XY).…”
Section: Methodsmentioning
confidence: 99%
“…Microsatellite and SNP markers have become in the last years the markers of choice for genetic analyses in grapevine, including genetic mapping and QTL identification (Huang et al 2012;Doligez et al 2013;Battilana et al 2013;Barba et al 2014), linkage disequilibrium and association analyses (Emanuelli et al 2010;Barnaud et al 2010;Cardoso et al 2012;Vargas et al 2013), and varietal identification (Myles et al 2010;Cabezas et al 2011;Laucou et al 2011;Migliaro et al 2012). As in many other woody plant species, genetic mapping in grapevine has been carried out using mainly the double pseudo test-cross strategy (Grattapaglia et al 1995), which is based on the study of allelic segregation of markers found in heterozygosis in one or both progenitors of an F 1 progeny.…”
Section: Applications Of the Developed Multiplex Pcrsmentioning
confidence: 99%
“…The availability of the grapevine genome sequence combined with the advent of cheaper and high throughput single nucleotide polymorphism (SNP) genotyping strategies (Gupta et al 2008;Davey et al 2011) were expected to shift the tools of genetic studies in grapevine. However, microsatellites are still the predominant markers contributing to the current knowledge of genetic determinism of the major grapevine traits (Mejía et al 2011;Huang et al 2012;Duchêne et al 2012;Karaagac et al 2012;Doligez et al 2013;Battilana et al 2013;Grzeskowiak et al 2013;Ban et al 2014;Correa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We observed only white berried bunches and could not observe any segregation. Also the region where sex of vine [19] is determined should be located at Chr.2 which we could not verify due to monomorphic hermaphrodite vines. Chromosome 3 could be defined by the use of 4 markers and the distribution is normal.…”
Section: Population 1929 (Grüner Veltliner X Malverina)mentioning
confidence: 81%